2023
DOI: 10.3390/ph16071006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Autophagy by Dapagliflozin Mitigates Cadmium-Induced Testicular Dysfunction in Rats: The Role of AMPK/mTOR and SIRT1/Nrf2/HO-1 Pathways

Abstract: Cadmium (Cd) is a widespread environmental pollutant that triggers testicular dysfunction. Dapagliflozin is a selective sodium-glucose co-transporter-2 inhibitor with notable antioxidant and anti-apoptotic features. It has shown marked cardio-, reno-, hepato-, and neuroprotective effects. Yet, its effect on Cd-evoked testicular impairment has not been examined. Hence, the goal of the current study was to investigate the potential positive effect of dapagliflozin against Cd-induced testicular dysfunction in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Virtually, evidence exists that autophagy activation is one mechanism underlying the protective effects of DPG against 3-nitropropionic acid-induced Huntington-like disease [17]. Likewise, it has been demonstrated that DPG possesses pro-autophagic properties that mediate the mitigation of renal injury [50], testicular injury [33], inflammatory bowel disease [34], and hepatic steatosis [35]. In previous animal models, activation of the AMPK/mTOR pro-autophagic pathway interceded autophagy stimulation [34,35,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually, evidence exists that autophagy activation is one mechanism underlying the protective effects of DPG against 3-nitropropionic acid-induced Huntington-like disease [17]. Likewise, it has been demonstrated that DPG possesses pro-autophagic properties that mediate the mitigation of renal injury [50], testicular injury [33], inflammatory bowel disease [34], and hepatic steatosis [35]. In previous animal models, activation of the AMPK/mTOR pro-autophagic pathway interceded autophagy stimulation [34,35,50].…”
Section: Discussionmentioning
confidence: 99%
“…A light microscopic examination (Leica Microsystems, Wetzlar, Germany) was performed by staining the tissue with H-E. In this regard, six fields were photographed in a non-overlapping manner [33,34].…”
Section: Histopathologymentioning
confidence: 99%